Microemulsion Formulation of Combination of Virgin Coconut Oil and Rice Bran Oil for Hair Growth - Wira Noviana Suhery; Mira Febrina; Ivone Permatasari (Faculty of Pharmacy, Universitas Gadjah Mada, 2018)
Research on micro emulsion formulation of combination of virgin coconut oil (VCO) and rice bran oil (RBO) as a hair growth promoter has been done. The purpose of this study was to formulate and produce the best formula that is physically stable and optimally promoting the hair growth by varying the content of VCO and RBO in the form of micro emulsions. These dosage formulations were prepared in three formulas using 45% tween 80 as surfactants and 20% glycerin as co surfactant i.e.: F,I containing a combination of VCO and RBO 1:1; FII (1:2) and FIII (2:1). Physical evaluation of the preparation was carried out for 8 weeks of storage which included organoleptic examination, pH, homogeneity, density, globule particle size, phase freeze thaw, and rabbit hair growth activity test for 18 days. Based on the results of the evaluation, it was found that the FI, FII and FIII micro emulsion formulations were physically stable for 8 weeks of storage with a pH ranging from 6.7 to 7.0, density of 1.085-1.088 g/mL, average globul particle size of FI (34.6 nm ), FII (54 nm) and FIII (68.8 nm). The best formulas is FIII for hair growth length of 1.26 cm for 18 days.